Implementation of Professionalism of Medical Faculty Students During Small Group Discussions in Qualitative Study - Sari, Paramita; Lestari, Marselli Widya (UNUSA Press, 2024)
Introduction: Medical science is developing very rapidly. One of the efforts to keep up with the development of medical science is to improve the quality of human resources in the health sector, especially in the medical field. However, efforts to improve the quality of human resources in the medical field are hampered because the implementation of professionalism in the field of medical education has not been achieved optimally. One of the basic foundations of the implementation of professionalism in medical students is professionalism during the teaching and learning process. Objective: This study aims to determine the implementation of the professionalism of medical faculty students during small group discussions in a qualitative study. Method: This study uses a qualitative method with a descriptive-analytical approach at the Faculty of Medicine, Nahdlatul Ulama University, Surabaya. Conducted for 3 weeks from June 25, 2024, to July 15, 2024, with 5 research respondents using purposive sampling. Data collection was carried out through in-depth interviews. Data analysis used a coding system with thematic analysis. Result: The Implementation of Professionalism of Medical Faculty Students during Small Group Discussions in Qualitative Study is influenced by two factors, namely supporting factors such as student personality, student environment, and supervisor, while less supportive factors such as limited facilities and infrastructure, certain students who have a negative influence on the learning environment, and students' readiness to receive courses. Conclusion: The implementation of student professionalism during small group discussions is influenced by several factors, so continuous holistic improvement is needed so that the values of professionalism as a doctor are possessed as early as possible.